Living together after genocide : a case study of reconciliation efforts in Burgesera District after 1994 Rwanda genocide. - Karegye, Kamili. (2010)
The overall objective of the research was to evaluate the achievements of reconciliation process in Bugesera district after the Rwandan 1994 genocide. Bugesera district lost over 62,000 Tutsi during genocide, being the most hit in the country. Today, the survivors and perpetrators are living together in the same district. The study is aimed at evaluating the impact of reconciliation mechanisms in place and how these mechanisms can be enhanced to get better results. The research was conducted in Bugesera district and qualitative research methods were adopted where by thirty respondents were interviewed; ten from the survivors , ten from released perpetrators of genocide, five district officials, three from NGOs and two church leaders. The research was based on both primary and secondary data, but primary data was used mostly. Most of the key concepts used in the research were explained in the literature review. From the research, it was revealed that efforts are in place to reconcile the survivors and perpetrators but people are still suspicious of one another. That a gap between survivors and perpetrators still exists, irrespective of government and patterns' efforts in bringing them together. The research suggested a number of recommendations, which would enhance reconciliation in the district. === Thesis (M.Comm.)-University of Kwazulu-Natal, 2008.